Profilin and Mical combine to impair F-actin assembly and promote disassembly and remodeling. - Grintsevich, E.E.; Ahmed, G.; Ginosyan, A.A.; Wu, H.; Rich, S.K.; Reisler, E.; Terman, J.R. (Nature communications, 2021)
Cellular events require the spatiotemporal interplay between actin assembly and actin disassembly. Yet, how different factors promote the integration of these two opposing processes is unclear. In particular, cellular monomeric (G)-actin is complexed with profilin, which inhibits spontaneous actin nucleation but fuels actin filament (F-actin) assembly by elongation-promoting factors (formins, Ena/VASP). In contrast, site-specific F-actin oxidation by Mical promotes F-actin disassembly and release of polymerization-impaired Mical-oxidized (Mox)-G-actin. Here we find that these two opposing processes connect with one another to orchestrate actin/cellular remodeling. Specifically, we find that profilin binds Mox-G-actin, yet these complexes do not fuel elongation factors'-mediated F-actin assembly, but instead inhibit polymerization and promote further Mox-F-actin disassembly. Using Drosophila as a model system, we show that similar profilin-Mical connections occur in vivo - where they underlie F-actin/cellular remodeling that accompanies Semaphorin-Plexin cellular/axon repulsion. Thus, profilin and Mical combine to impair F-actin assembly and promote F-actin disassembly, while concomitantly facilitating cellular remodeling and plasticity.